INTAN: An Interactive Digital Learning Medium for Improving Elementary Students' Fraction Understanding Through Multi-Modal Pedagogical Design - Dewi, Intan Silvia; Airlanda, Gamaliel Septian (Journal of Innovation and Research in Primary Education, 2025)
Fraction comprehension represents a fundamental challenge in elementary mathematics education, with students frequently struggling to understand abstract concepts such as equivalence and representation. Traditional instructional methods often fail to provide adequate conceptual foundations, leading to procedural learning approaches prone to errors. This study developed INTAN (Interactive Numerical Training for Advancing Fraction), an innovative digital learning medium integrating Visual, Auditory, and Kinesthetic (VAK) learning approaches to improve fraction understanding among third-grade students. The research employed a Research and Development methodology following the Borg and Gall model through six stages: research and data collection, planning, product development, expert validation, revision, and field testing. Expert validation involved three specialists evaluating content, media, and language appropriateness using Likert-scale instruments. Field testing was conducted with 20 third-grade students at SD Karunia Global School Jambi using pre-test and post-test assessments aligned with Cambridge Curriculum standards. Data analysis included descriptive statistics, normality testing, and paired-samples t-tests. Expert validation demonstrated high feasibility with validity percentages of 82% (content), 88% (media), and 96% (language). Field testing revealed significant learning improvements, with mean scores increasing from 62.70 to 80.30 (p < 0.001). Performance variability decreased substantially, indicating particular benefits for struggling learners while maintaining high achievement among stronger students. INTAN effectively addresses persistent challenges in fraction education through multi-modal learning integration and adaptive gamification elements. The findings support theoretical frameworks emphasizing conceptual understanding before procedural skill development while demonstrating the potential of well-designed educational technology to enhance student engagement and learning outcomes in mathematics instruction.